2014
DOI: 10.1111/vop.12243
|View full text |Cite
|
Sign up to set email alerts
|

Retinal dysplasia inAmerican pit bull terriers – phenotypic characterization and breeding study

Abstract: This is a report of a novel inherited form of RD that affects American pit bull terriers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…The disease is inherited as autosomal dominant, and affected dogs are shorter in stature and have a spectrum of retinal lesions ranging from multifocal and geographic lesions to retinal detachment. To date, the disease‐causing gene/mutation has not been identified …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disease is inherited as autosomal dominant, and affected dogs are shorter in stature and have a spectrum of retinal lesions ranging from multifocal and geographic lesions to retinal detachment. To date, the disease‐causing gene/mutation has not been identified …”
Section: Introductionmentioning
confidence: 99%
“…To date, the disease-causing gene/mutation has not been identified. 26 Because most of the milder phenotypes associated with RD, focal/multifocal folds or geographic lesions, cause little or no visual impairment, there is a paucity of histologic studies that can complement the clinically observed fundus changes. A detailed histologic study of retinal folds in the Beagle has been carried out, 27 but, to our knowledge, the structural lesions of geographic RD have yet to be reported.…”
mentioning
confidence: 99%
“…The second modality is spectral domain optical coherence tomography (SD‐OCT), which allows clinicians to measure the thickness of the retina and its layers in order to determine structural damage prior to RRS . As SD‐OCT is becoming available to more veterinary ophthalmologists, albeit currently mostly in universities, veterinary retinal surgeons may soon have the option of referring their patients to pre‐operative retinal scans that may help determine the prognosis for postoperative vision. However, based on our results that all dogs with a recordable pre‐operative ERG regain normal vision compared to 64% of dogs with a nonrecordable pre‐operative ERG (Table ) it seems that the widely available flash ERG can also serve as a prognostic indicator in RRS.…”
Section: Discussionmentioning
confidence: 99%
“…In humans with retinal disorders, the use of OCT is common and many studies evaluating the optic nerve head, retinal nerve fiber layer, and macula have been performed 2 . Veterinary use of OCT has been reported frequently in mammals such as dogs and cats 3‐10 . The relationship between retinal structure abnormalities and vision‐related diseases including retinal dysplasia, 8 progressive retinal atrophy, 9 sudden acquired retinal degeneration syndrome (SARDS), 10 and glaucoma 3 has been studied in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Veterinary use of OCT has been reported frequently in mammals such as dogs and cats 3‐10 . The relationship between retinal structure abnormalities and vision‐related diseases including retinal dysplasia, 8 progressive retinal atrophy, 9 sudden acquired retinal degeneration syndrome (SARDS), 10 and glaucoma 3 has been studied in dogs. There are a few studies on reptilian species (saurians, ophidians, and chelonians) 11,12 .…”
Section: Introductionmentioning
confidence: 99%